IL-9 Integrates the Host-Candida Cross-Talk in Vulvovaginal Candidiasis to Balance Inflammation and Tolerance - Renga, Giorgia; Borghi, Monica; Oikonomou, Vasileios; Mosci, Paolo; Bartoli, Andrea; Renauld, Jean-Christophe; Romani, Luigina; Costantini, Claudio (Frontiers in Immunology, 2018)
Vulvovaginal candidiasis (VVC) is a common fungal infection caused by Candida albicans. The antifungal therapy represents the standard of care but due to the high costs of treatment and to the inability to prevent recurrences, the development of alternative therapeutic approaches is much-awaited. Recently, we have shown that the pathogenesis of C. albicans in the gut is modulated by IL-9, a pleiotropic cytokine able to promote both inflammation and tolerance during C. albicans infection. Herein, by using a mouse model of VVC, we similarly demonstrated that IL-9 might exert a dual role in VVC by contributing to inflammation during the initial immune activation and promoting resolution thereafter. Specifically, IL-9 has a pro-inflammatory activity at the onset of VVC by promoting NLRP3 inflammasome activity and mucosal mast cells expansion but a tolerogenic role in the resolution phase by promoting IL-1Ra production and connective tissue mast cells activation. We further show that a timely IL-9 neutralization at the onset of the inflammatory response ameliorated symptoms and vaginal pathology. Given that vaginal fluids from patients with recurrent VVC had higher levels of IL-9, these findings, by providing novel insights into the pathogenesis of VVC, may pave the way for alternative therapeutic strategies based on IL-9 neutralization.